Systematic consideration of floral microcharacters of the south american genus chrysolaena (vernonieae, asteraceae) - Via Do Pico, Gisela Mariel (2016)
Fil: Via Do Pico, Gisela Mariel. Universidad Nacional del Nordeste. Facultad de Ciencias Agrarias; Argentina.